Sarcopenic Obesity in Children and Adolescents: A Systematic Review - Zembura, Marcela; Matusik, Paweł (Frontiers in Endocrinology, 2022)
Sarcopenic obesity (SO) is defined as co-occurrence of increased fat mass and sarcopenia and may predict adverse health outcomes in pediatric population. However, the prevalence of SO and its association with adverse health outcomes have not been well defined in children and adolescents. We systematically reviewed data on the SO definition, prevalence and adverse outcomes in pediatric population. A total of 18 articles retrieved from PubMed or Web of Science databases were included. Overall, there was a wide heterogeneity in the methods and thresholds used to define SO. The prevalence of SO ranged from 5.66% to 69.7% in girls, with a range between 7.2% and 81.3% in boys. Of the 8 studies that evaluated outcomes related with SO, all showed a significant association of SO with cardiometabolic outcomes, nonalcoholic fatty liver disease (NAFLD) severity, inflammation and mental health. In conclusion, this review found that SO is highly prevalent in children and adolescents and is associated with various adverse health outcomes. Findings of this review highlight the need for development of consensus regarding definition, standardized evaluation methods and age and gender thresholds for SO for different ethnicities in pediatric population. Further studies are needed to understand the relationship between obesity and sarcopenia and SO impact on adverse health outcomes in children and adolescents.